Systemic inflammatory response after hyperthermic intraperitoneal chemotherapy (HIPEC): The perfusion protocol matters!. Issue 9 (September 2019) - Roth, Lilian; Eshmuminov, Dilmurodjon; Laminger, Felix; Koppitsch, Claudia; Schneider, Marcel; Graf, Theresia Reding; Gupta, Anurag; Kober, Fritz; Roka, Sebastian; Gertsch, Philippe; Lehmann, Kuno
Abstract: Background: CRS/HIPEC gained acceptance as a treatment for selected patients with peritoneal metastasis. However, the pathophysiology behind HIPEC is poorly understood, and a variety of regimens are currently in use. In this study, we describe for the first-time changes in the postoperative systemic inflammatory reaction, highly different among HIPEC treatment protocols. Methods: HIPEC was performed with three protocols, different with regard to perfusion times and drugs: (mitomycinC/doxorubicin, 90min), (cisplatin, 90min) (oxaliplatin, 30min). Serial blood samples were assessed for C-reactive protein (CRP), white blood cells (WBC), pancreatic stone protein (PSP) and bacterial component (16s rDNA). The study was approved by the local ethics committee and registered at clinicaltirals.gov (NCT02741167). Results: Overall, 140 patients from two European centers were included. In patients without postoperative complications, a secondary peak of inflammatory parameters, CRP (p = 0.015) and PSP (p = 0.004) was observed after HIPEC for 90 min with mitomycinC/doxorubicin or cisplatin but not after 30 min oxaliplatin. In patients after 90 min HIPEC, postoperative serum bacterial 16srDNA level were 2.1 times higher (95% CI 0.646–3.032, p = 0.015) compared to 30 min oxaliplatin. Discussion: In conclusion, we identified a secondary inflammatory reaction after 90 min HIPEC, either with mitomycinC/doxorubicin or cisplatin, not observed after short course HIPEC with oxaliplatin. This protocol dependent physiology of acute phase proteins should be known in the clinical management of patients after HIPEC.